The Impact Of Climate Change On Productivity and Food Security In Indonesia - sihombing, vista uli; Ulidesi Siadari; Ratna Sari; Muhtar Ardansah Munthe (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
El Nino (drought) and La Nina (floods) effects of climate change will significantly reduce production and productivity in the agricultural sector, particularly in food crops. The availability and accessibility of food will be impacted by climate change, disrupting food security and vulnerability. This research aims to examine in more depth the impacts caused by climate change and ways that can be taken to mitigate the risks posed. This research was carried out using the PAR (Participatory Action Research) method through FGD (Forum Group Discussion), which was carried out with representative experts, such as academics, farmers, BULOG and BMKG. The results of the research show that there are many impacts caused by climate change on food security, such as drought and floods resulting in changes in the planting season, an increase in weeds, pests and diseases in plants, and increasing temperatures will cause crop productivity to decrease, causing a decrease in crop yields. So, in facing the challenges and impacts of climate change, there needs to be significant and continuous collaboration from all aspects of dealing with climate change so that food security is achieved. Providing complete information to farmers regarding the challenges and solutions in facing climate change, research that can be carried out to reduce and mitigate climate change, the existence of adequate availability aspects to support universal food security and agricultural adaptation in facing climate change as well as climate change adaptation strategies indispensable for sustainable food security